1990
DOI: 10.1111/j.1365-2230.1990.tb02108.x
|View full text |Cite
|
Sign up to set email alerts
|

Lichen planus in children-a review of six cases

Abstract: We present the features of six children who have been seen amongst 154 consecutive new patients with lichen planus in our outpatients clinic. All but one of the children had unusual forms of the disease and there was a family history of lichen planus in three. Lichen planus is rare in childhood and often assumes atypical clinical patterns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
49
0
4

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 3 publications
3
49
0
4
Order By: Relevance
“…4 In fact, the limited data from Europe suggest that children of Indian descent are overrepresented among childhood LP cases in this region as well. 6,30 That there is an increased incidence in Indian children in Europe and in India suggests a possible genetic origin as opposed to a strictly environmental one.…”
Section: Pathogenesismentioning
confidence: 96%
See 1 more Smart Citation
“…4 In fact, the limited data from Europe suggest that children of Indian descent are overrepresented among childhood LP cases in this region as well. 6,30 That there is an increased incidence in Indian children in Europe and in India suggests a possible genetic origin as opposed to a strictly environmental one.…”
Section: Pathogenesismentioning
confidence: 96%
“…29 Although controlled studies are lacking, there appears to be a possible increase in childhood LP in Indian and Arab children relative to European children, as mentioned earlier. 2,6,7 There has been speculation that this may be because of environmental factors, such as hepatitis C being more prevalent in Indian childhood LP. 30 However, there is no increase in hepatitis C among Indian childhood LP cases studied to date.…”
Section: Pathogenesismentioning
confidence: 97%
“…Cutaneous LP in childhood is an uncommonly encountered dermatosis5 8 10 11 and is extremely rare in infancy 12. Studies of children with mucocutaneous LP have still shown a very low incidence of oral involvement 4 8 9.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of children with mucocutaneous LP have still shown a very low incidence of oral involvement 4 8 9. Familial LP has been reported as being uncommon 5 10 13. Childhood familial LP is said to occur at an early age and with greater severity 10.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation